Traceability permissioned chain consensus mechanism based on double-layer architecture - Qingyang DING; Jianming ZHU; Jin ZHANG; Biao SONG; Yanjing XU; Chuanchang JIA; Zheng GAO (网络与信息安全学报)
The blocks in the blockchain are arranged in chronological and historical order,and the blockchain is incapable of modification through data encryption technology and consensus mechanism,which makes product trace ability to be an important application scenario of blockchain.To choose product information traceability technology,not only the feasibility of the technology but also the market attributes of the product and the producer should be considered,which makes the permissioned chain replace the public chain as an important deployment method of product information traceability.In the existing research results,the research on the traceability license chain mainly focuses on mechanism design and framework construction,and the consensus algorithm applicable to product information traceability is rarely studied.In the process of technology of engineering practice,practical byzantine fault tolerance was chosen more in league chain as the consensus of traceability chain mechanism (such as Hyperledger),but with the increasing number of participating nodes of the traceability chain efficiency will be significantly reduced,and the delay time will be significantly improved,resulting in most of the project is still in the stage of experiment.Based on this,a traceability license chain consensus mechanism based on double-layer architecture (DLPCM) is proposed,and its security is analyzed.Participants are divided into two layers on the vertical dimension,and different consensus mechanisms are adopted at different levels according to different deployment modes of blockchain.Finally,the traceability information query mechanism under the consensus mechanism is introduced,an important reference for the development and design of traceability system based on license chain is provided.